2019
DOI: 10.3389/fphys.2019.00532
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial (Dys)function and Insulin Resistance: From Pathophysiological Molecular Mechanisms to the Impact of Diet

Abstract: Mitochondrial dysfunction has been implicated in the pathogenesis of insulin resistance, the hallmark of type 2 diabetes mellitus (T2DM). However, the cause-effect relationship remains to be fully elucidated. Compelling evidence suggests that boosting mitochondrial function may represent a valuable therapeutic tool to improve insulin sensitivity. Mitochondria are highly dynamic organelles, which adapt to short- and long-term metabolic perturbations by undergoing fusion and fission cycles, spatial rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(208 citation statements)
references
References 206 publications
(272 reference statements)
10
195
0
3
Order By: Relevance
“…The presented results confirm the different biological (anti-inflammatory and antioxidant) effects elicited by individual CLA isomers in this animal model of diet-induced obesity [26] and extend their different modulatory effects on metabolic flexibility in skeletal muscle. The recognized role of skeletal muscle in metabolic flexibility, due to the association of muscular mitochondrial dysfunction with insulin resistance [56], prompted us to evaluate individual CLA isomers' (C9 and C10) efficacy in modulating mitochondrial function and efficiency in this tissue. The current results show, for the first time, that CLA isomer supplementation exhibits beneficial effects on several typical features of HFD-induced metabolic inflexibility (i.e., increased metabolic efficiency, weight gain, and body lipid levels; glucose and lipid homeostasis disruption; pro-inflammatory effects) via different mechanisms and with distinct efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The presented results confirm the different biological (anti-inflammatory and antioxidant) effects elicited by individual CLA isomers in this animal model of diet-induced obesity [26] and extend their different modulatory effects on metabolic flexibility in skeletal muscle. The recognized role of skeletal muscle in metabolic flexibility, due to the association of muscular mitochondrial dysfunction with insulin resistance [56], prompted us to evaluate individual CLA isomers' (C9 and C10) efficacy in modulating mitochondrial function and efficiency in this tissue. The current results show, for the first time, that CLA isomer supplementation exhibits beneficial effects on several typical features of HFD-induced metabolic inflexibility (i.e., increased metabolic efficiency, weight gain, and body lipid levels; glucose and lipid homeostasis disruption; pro-inflammatory effects) via different mechanisms and with distinct efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, many studies have observed reduced skeletal muscle mitochondrial mass in obesity and T2DM , as well as decreased maximal respiration rates in skeletal muscle from T2DM . In fact, it is suggested that mitochondrial dysfunction may be a causative factor for the impairment in insulin intracellular signaling pathway, and to the development of insulin resistance . Mitochondrial function is related to fatty acid transport, acetyl‐CoA and fatty acid synthesis, β‐oxidation and electron transport chain activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inhibition of Drp1-dependent mitochondrial fission in the DVC of HFD-fed rodents prevents hyperphagia and body weight gain and restores insulin sensitivity in a diet-induced obesity model. Indeed, mitochondrial dynamics governed by Drp1 also regulates energy metabolism in other tissues, for instance, insulin sensitivity and mitochondria fragmentation in muscle causes insulin resistance and metabolic imbalance in HFD-fed and obese rodent models (Touvier et al, 2015;Bratic & Trifunovic, 2010;Sergi et al, 2019). Thus, the mechanistic insights revealed here, are likely to be relevant to other organs and tissues, and may represent a unifying model by which mitochondria regulates glucose metabolism, insulin signalling and body weight.…”
Section: Figure 6: Summary Of Drp1 Regulation Of Insulin Resistance Amentioning
confidence: 77%